Eco-efficiency analysis for remote area power supply selection in Western Australia - Arceo, Aldrick; Rosano, Michele; Biswas, Wahidul (2018)
Remote area power supply (RAPS) systems in Western Australia account for more than 56% of total off-grid electricity supply in Australia and utilise carbon emission intensive diesel and gas generating technologies for power supply. Most of these RAPS systems are run by environmentally unfriendly conventional fuel due to economic reasons. An eco-efficiency analysis (EEA) framework was therefore developed to explore the environmental and economic efficiency of the current diesel RAPS systems in Western Australia. ISO 14040:2006 for Life Cycle Assessment and AS/NZS 4536:1000 (R2014) for Life Cycle Costing have been used to estimate the associated environmental impacts and costs of RAPS systems in conducting an EEA. The results show that the integration of solar photovoltaic panels and an energy storage system into existing diesel generating units for power supply could improve the eco-efficiency of the existing system. It was found that a 4% increase in total life cycle costs with the use of a hybrid system could potentially decrease the overall environmental impacts by 16%.